1992
DOI: 10.1111/j.1574-6968.1992.tb04988.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relative importance of specific and non-specific approaches to oral microbial adhesion

Abstract: In this paper, it is suggested that specificity and non‐specificity in (oral) microbial adhesion are different expressions for the same phenomena. It is argued that the same basic, physico‐chemical forces are responsible for so‐called ‘non‐specific’ and ‘specific’ binding and that from a physico‐chemical point of view the distinction between the two is an artificial one. Non‐specific interactions arise from Van der Waals and electrostatic forces and hydrogen bonding, and originate from the entire cell. A speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 75 publications
(58 reference statements)
1
55
0
Order By: Relevance
“…Although VPs will become covered by a conditioning film of adsorbed salivary components prior to adhesion of bacteria or yeasts, experiments in the human oral cavity have demonstrated that the properties of this conditioning film are determined by the material itself (Busscher et al, 1992(Busscher et al, , 1997a. Biofilm formation may therefore be influenced by adjusting the properties of the VPs material, by surface modification, and thus a number of strategies have been employed.…”
Section: Modifications Of Silicone Rubber Surfacesmentioning
confidence: 99%
“…Although VPs will become covered by a conditioning film of adsorbed salivary components prior to adhesion of bacteria or yeasts, experiments in the human oral cavity have demonstrated that the properties of this conditioning film are determined by the material itself (Busscher et al, 1992(Busscher et al, , 1997a. Biofilm formation may therefore be influenced by adjusting the properties of the VPs material, by surface modification, and thus a number of strategies have been employed.…”
Section: Modifications Of Silicone Rubber Surfacesmentioning
confidence: 99%
“…Biofilm formation continues with the transport of cells to the substratum:liquid interface, which is governed by a combination of transport mechanisms (i.e., diffusion, convection, sedimentation, and motility) (Bryers, 2000). Once at a substratum surface, bacterial cells adhere by non-specific and/or specific receptor:ligand adhesion mechanisms (An and Friedman, 1998;Busscher et al, 1992;Glantz et al, 1999). Within minutes of attachment, adherent cells up-regulate the secretion of certain cell signal molecules that orchestrate communitywide phenotypic responses, through a process termed quorum sensing (Bjarnsholt and Givskov, 2007;Camilli and Bassler, 2006;Davies et al, 1998;Harraghy et al, 2007;Hodgkinson et al, 2007;Horswill et al, 2007;Pritchard, 2006;Rumbaugh, 2007).…”
Section: Processes Governing Biofilm Formationmentioning
confidence: 99%
“…Colonization of enamel surfaces by the cariogenic bacteria is thought to be initiated by attachment to a saliva-derived conditioning film, the acquired enamel pellicle (AEP) (Gibbons and Qureshi 1976). The AEP is formed largely by adsorption of many heterogeneous salivary proteins (Mogi et al 1986;Al-Hashimi and Levine 1989) on to dental enamel and promotes the adhesion of S. mutans by specific (Liljemark and Bloomquist 1996;Bowden and Hamilton 1998) and nonspecific mechanisms (Busscher et al 1992). This is followed by multiplication and exopolysaccharide formation by the bacteria to form a biofilm.…”
Section: Introductionmentioning
confidence: 99%